The fetal ovary exhibits temporal sensitivity to a ‘real-life’ mixture of environmental chemicals - Leach, Richard G.; Amezaga, Maria R.; Loup, Benoit; Mandon-Pépin, Béatrice; Stefansdottir, Agnes; Filis, Panagiotis; Kyle, Carol; Zhang, Zulin; Allen, Ceri E.; Purdie, Laura; Jouneau, Luc; Cotinot, Corinne; et al. (Nature Publishing Group, 2016)
The development of fetal ovarian follicles is a critical determinant of adult female reproductive competence. Prolonged exposure to environmental chemicals (ECs) can perturb this process with detrimental consequences for offspring. Here we report on the exposure of pregnant ewes to an environmental mixture of ECs derived from pastures fertilized with sewage sludge (biosolids): a common global agricultural practice. Exposure of pregnant ewes to ECs over 80 day periods during early, mid or late gestation reduced the proportion of healthy early stage fetal follicles comprising the ovarian reserve. Mid and late gestation EC exposures had the most marked effects, disturbing maternal and fetal liver chemical profiles, masculinising fetal anogenital distance and greatly increasing the number of altered fetal ovarian genes and proteins. In conclusion, differential temporal sensitivity of the fetus and its ovaries to EC mixtures has implications for adult ovarian function following adverse exposures during pregnancy.